Forgoing New Public Management and Adopting Post‐New Public Management Principles: The On‐Going Civil Service Reform in Israel. (February 2016) - Cohen, Nissim
Summary: Since the 1980s, New Public Management (NPM) and post‐NPM reforms have dominated attempts to improve public administration. The literature suggests several reasons for the latter approach. However, these explanations seem to be less relevant to the ongoing civil service reforms in Israel. The Israeli experience is an example where NPM reforms did not occur, but post‐NPM reforms were adopted enthusiastically decades later. Our findings demonstrate how under the structural conditions of both non‐governability and bureaucratic centralization, post‐NPM reforms may provide an attractive layering strategy, offering the option of changing certain features of the system without requiring a drastic, comprehensive overhaul of it. Once Israeli decision makers decided that there was a real public demand for reform, and long‐term learning and diffusion processes convinced them that change was needed, the characteristics of the post‐NPM approach made it much easier politically for them to adopt. Copyright © 2016 John Wiley & Sons, Ltd.